Migration, social standards and replacement incomes : how to protect low-income workers in the industrialized countries against the forces of globalization and market integration - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper discusses how an industrialized country could defend the wages and social benefits of its unskilled workers against wage competition from immigrants. It shows that fixing social standards harms the workers and that fixing social replacement incomes implies migration into unemployment. Defending wages with replacement incomes brings about first-order efficiency losses that outweigh the budget cost to the government. By contrast, wage subsidies involve much smaller welfare losses. While the exclusion of migrants from a national replacement program does not improve the situation, the (temporary) exclusion of migrants from a national subsidy program makes it possible to avoid a distortion of the migration pattern.
Keywords: I38; F22; J61; H5; F15; 330; migration; unemployment; welfare; Standortwettbewerb; Sozialstaat; Internationale Sozialstandards; Internationale Arbeitsmobilität; Theorie; Industriestaaten